Noncoding RNAs as a novel approach to target retinopathy of prematurity - Kim, Hyunjong; Kim, Jaesub; Ryu, Juhee (Frontiers in Pharmacology, 2022)
Retinopathy of prematurity (ROP), a vascular disease characterized by abnormal vessel development in the retina, has become a primary cause of blindness in children around the world. ROP can be developed during two different phases: vessel loss and vessel proliferation. Once preterm infants with immature retinal vessel growth are exposed to high level of oxygen inside the incubator, vessel loss can occur. When infants are exposed to room air, they may experience the proliferation of vessels in the retina. Although multiple factors are reported to be involved in the pathogenesis of ROP, including vaso-endothelial growth factors (VEGFs) and hypoxia-inducible factors, the pathogenesis of ROP is not completely understood. Although laser therapy and pharmacologic agents, such as anti-VEGF agents, have been commonly used to treat ROP, the incidence of ROP is rapidly rising. Given that current therapies can be invasive and long-term effects are not fully known, the search for novel therapeutic targets with less destructive properties needs to be considered. Within the last decade, the field of noncoding RNA therapy has shown potential as next-generation therapy to treat several different diseases. In this review, we introduce various noncoding RNAs regulating ROP and discuss their role as potential therapeutic targets in ROP.